Different Non-Saccharomyces Yeast Species Stimulate Nutrient Consumption in S. cerevisiae Mixed Cultures - Curiel, Jose A.; Morales, Pilar; Gonzalez, Ramon; Tronchoni, Jordi (Frontiers in Microbiology, 2017)
The growing interest of the winemaking industry on the use of non-Saccharomyces starters has prompted several studies about the physiological features of this diverse group of microorganisms. The fact that the proposed use of these new starters will almost invariably involve either simultaneous or sequential inoculation with Saccharomyces cerevisiae has also driven the attention to the potential biological interactions between different starters during wine fermentation. Our current understanding is that alternative yeast starters will affect wine features by both direct and indirect mechanisms (through metabolic or other types of interactions with S. cerevisiae). There are still few studies addressing the question of yeast-yeast interactions in winemaking by a transcriptomic approach. In a previous report, we revealed early responses of S. cerevisiae and T. delbrueckii to the presence of each other under anaerobic conditions, mainly the overexpression of genes related with sugar consumption and cell proliferation. We have now studied the response, under aerobic conditions, of S. cerevisiae to other two non-Saccharomcyes species, Hanseniaspora uvarum and Candida sake, keeping T. delbrueckii as a reference; always focusing on the early stages of the interaction. Results point to some common features of the way S. cerevisiae modifies its transcriptome in front of other yeast species, namely activation of glucose and nitrogen metabolism, being the later specific for aerobic conditions.